Underwater communications using virtual time reversal in a variable geometry channel - Silva, A. (2014)
Field experiments using Time-Reversal Mirror( TRM) techniques have shown that the underwater acoustic channel presents a longer stability than it was previously anticipated. Applying such techniques to underwater communications requires that, either the emitted signals are previously ltered by time-reversed replicas of the channel impulse response or that a probe-signal should be transmitted ahead of the data-signal for post channel ltering. In the former case, the time-reversed ltered message is expected to be undone by the actual acoustic channel between the array and the receiver, while in the later, the undoing of the multipath is performed electronically inside the computer and is therefore termed as virtual Time Reversal Mirror(vTRM). The main issues being addressed in recent literature deal with channel stability, focus width and the required array aperture for obtaining reasonable temporal and/or spatial focusing. This paper focus essentially in two practical aspects, generally not addressed: one is to demonstrate the potential application of the vTRM approach to undo the severe intersymbol interference in a real variable geometry channel scenario and, the other, is the importance of optimization of the probe-signal time window length in a real application.